A Multi-Scenario Forecast of Urban Change: A Study on Urban Growth in the Algarve - Eric de Noronha Vaz; Peter Nijkamp; Marco Painho; Mario Gaetano (Tinbergen Institute, 2011)
The Algarve region in Portugal is often considered as one of the most appealing regions for tourism in the country. Its attractive location and moderate climate have since the mid-1960s brought increasing economic prosperity. As a result of the development of mass tourism, available land-use resources were widely exploited to create an integrated tourist industry. This region has shown an increasing loss of ecosystems resulting from the expansion of urban areas. This has also been accompanied by a significant abandonment of rural areas and hinterlands, leading to loss of agriculture and other rural activities. Clearly, urban growth needs considerable attention in the context of sustainable development, as often peri-urban areas with fragile ecosystems are becoming increasingly vulnerable. This paper aims to develop and apply key tools to quantify the changes of land use and how this affects the regional spatial scope by using multi-temporal inventorying an d accounting of land-use change matrices. Using Cellular Automata and a combined interpretation of CORINE Land Cover Data, it converges into a qualitative to quantitative interpretation of land use change by means of Multi-Criteria Evaluation. Finally, our analysis to identify the scenario with the best fit, based on the evolution of the actual 2006 land cover, enabled us to build a future urban growth model for 2020 which was quantitatively assessed. The outcome suggests a picture of continuing growth for the region of the Algarve within the framework of current policies and regressive spatial trends.
urn:NBN:nl:ui:31-1871/38547
Keywords: R11; R14; C50; 330; Urban growth; Algarve; CORINE Land Cover; Scenario modelling; Stadtentwicklung; Algarve